Naloxone receipt and overdose prevention care among people with HIV on chronic opioid therapy. (15th March 2021) - Kimmel, Simeon D.; Walley, Alexander Y.; Lodi, Sara; Forman, Leah S.; Liebschutz, Jane M.; Lira, Marlene C.; Kim, Theresa W.; del Rio, Carlos; Samet, Jeffrey H.; Tsui, Judith I.
Abstract : This cross-sectional study describes naloxone rescue kit receipt among people with HIV (PWH) on chronic opioid therapy (COT) and HIV clinician opioid overdose prevention care in two clinics between 2015 and 2017. Naloxone rescue kit receipt was uncommon. History of overdose was associated with receiving naloxone but having a clinician who reported providing overdose prevention care was not. This study suggests that clinicians prescribing COT to PWH should improve overdose prevention care, including naloxone co-prescribing.